Expression of placental glycans and its role in regulating peripheral blood NK cells during preeclampsia: a perspective - Bueno-Sánchez, Julio C.; Gómez-Gutiérrez, Alejandra M.; Maldonado-Estrada, Juan G.; Quintana-Castillo, Juan C. (Frontiers in Endocrinology, 2023)
Preeclampsia is a pregnancy-related multisystem disorder characterized by altered trophoblast invasion, oxidative stress, exacerbation of systemic inflammatory response, and endothelial damage. The pathogenesis includes hypertension and mild-to-severe microangiopathy in the kidney, liver, placenta, and brain. The main mechanisms involved in its pathogenesis have been proposed to limit trophoblast invasion and increase the release of extracellular vesicles from the syncytiotrophoblast into the maternal circulation, exacerbating the systemic inflammatory response. The placenta expresses glycans as part of its development and maternal immune tolerance during gestation. The expression profile of glycans at the maternal–fetal interface may play a fundamental role in pregnancy physiological changes and disorders such as preeclampsia. It is unclear whether glycans and their lectin-like receptors are involved in the mechanisms of maternal–fetal recognition by immune cells during pregnancy homeostasis. The expression profile of glycans appears to be altered in hypertensive disorders of pregnancy, which could lead to alterations in the placental microenvironment and vascular endothelium in pregnancy conditions such as preeclampsia. Glycans with immunomodulatory properties at the maternal–fetal interface are altered in early-onset severe preeclampsia, implying that innate immune system components, such as NK cells, exacerbate the systemic inflammatory response observed in preeclampsia. In this article, we discuss the evidence for the role of glycans in gestational physiology and the perspective of glycobiology on the pathophysiology of hypertensive disorders in gestation.